Una fuente inédita para el estudio del ayllu y el parentesco en los Andes surperuanos: Los libros parroquiales de la iglesia San Francisco de Asís de Marcapata (Quispicanchi, Cuzco, Perú) - Sendón, Pablo F. (Pontificia Universidad Católica del Perú, 2024)
The article presents and examines the marriage and baptismal records preserved in the parish of San Francisco de Asís, in the district of Marcapata (Quispicanchi, Cuzco), with the aim of exploring their potential for studying ayllu and kinship relations among the local population in the nineteenth and twentieth centuries. The analysis begins with an examination of the official census data available for the district and its constituent units as an introduction to the information contained in the parish records. When subjected to a genealogical reading, the records prove to be a highly valuable source for identifying kinship networks with exceptional potential exploration for studies focused on the social morphology of peasant indigenous populations in this region of the southern Peruvian Andes. A preliminary analysis of these networks –paying particular attention to the places of birth and residence of individuals, the distribution of principal surnames, and rates of endogamy and exogamy down to the district level– provides an alternative view of district organization that differs from official sources.

El artículo presenta y discute los libros de matrimonio y bautismo conservados en la parroquia San Francisco de Asís del distrito de Marcapata (Quispicanchi, Cuzco) con el propósito de explorar sus posibilidades para el estudio del ayllu y el parentesco entre la población local a lo largo de los siglos XIX y XX. Se parte de un análisis de la información censal oficial disponible acerca del distrito y de sus unidades constitutivas a modo de introducir la información contenida en los libros parroquiales. Sometidos a una lectura genealógica, los libros demuestran ser una fuente de gran utilidad para la identificación de redes de parentesco con posibilidades exploratorias excepcionales para los estudios interesados en la morfología social de las poblaciones campesino-indígenas de esta región de los Andes surperuanos. A partir de un análisis preliminar de estas redes —en el que se presta especial atención a los lugares de nacimiento y residencia de los individuos registrados en ellas, la distribución de los principales patronímicos y las tasas de endogamia y exogamia hasta el nivel del distrito— es posible acceder a un panorama de la conformación distrital alternativa a la que registran las fuentes oficiales.
An unpublished source for the study of the ayllu and kinship in the southern Peruvian Andes: The parish records of the San Francisco de Asís church, Marcapata (Quispicanchi, Cuzco, Peru)
Keywords: Parish books; Ayllu; Kinship; Peasant communities; Southern Peru; Libros parroquiales; Ayllu; Parentesco; Comunidades campesinas; Surperuano; https://purl.org/pe-repo/ocde/ford#6.01.01